2015
DOI: 10.3899/jrheum.141070
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Macitentan and Its Active Metabolite on Cultured Human Systemic Sclerosis and Control Skin Fibroblasts

Abstract: Macitentan and ACT-132577 seem to downregulate in vitro the profibrotic myofibroblast phenotype induced by ET-1 in cultured human SSc skin fibroblasts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…These data provide a novel mechanistic interaction between TGF-β and ET-1 and support the concept that ET-1 may play an important pathogenetic role during the earliest stages of development of fibrotic processes involving TGF-β-mediated EndoMT. These results also expand the previously described interactions between TGF-β and ET-1 during normal tissue repair reactions or in the course of organ-specific or systemic pathologic fibrogenesis [5964]. …”
Section: Discussionsupporting
confidence: 88%
“…These data provide a novel mechanistic interaction between TGF-β and ET-1 and support the concept that ET-1 may play an important pathogenetic role during the earliest stages of development of fibrotic processes involving TGF-β-mediated EndoMT. These results also expand the previously described interactions between TGF-β and ET-1 during normal tissue repair reactions or in the course of organ-specific or systemic pathologic fibrogenesis [5964]. …”
Section: Discussionsupporting
confidence: 88%
“…It has been demonstrated that ET receptor antagonists ameliorate bleomycin-induced pulmonary fibrosis [8]. Moreover, in a model of systemic sclerosis (SSc), macitentan inhibited the pro-fibrotic myofibroblast phenotype induced by ET-1 in human skin fibroblasts [25]. Circulating or tissue ET-1 levels are upregulated in IPF and SSc patients and in the bleomycin model of pulmonary fibrosis [26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, for severe RP and for prevention of DU onset and treatment of PAH, both intravenous (IV) prostanoid iloprost (ILO) and the dual endothelin-1 receptor antagonist (ERA) bosentan (BOSE) are used, respectively 10 . BOSE seems to block pathogenic activities of endothelin-1, the endothelial-derived mediator determining both vasoconstriction and fibrosis genes induction 11,12,13,14 .…”
Section: Rheumatologymentioning
confidence: 99%